Investigating the Pore Structure Characteristics and Reservoir Capacities of Lower Jurassic Continental Shale Reservoirs in the Northeastern Sichuan Basin, China - Jiang, Tao; Jin, Zhijun; Liu, Guangxiang; Hu, Zongquan; Chen, Xuanhua; Liu, Zhongbao; Wang, Guanping (Frontiers in Earth Science, 2022)
The Lower Jurassic shale in the northeastern Sichuan Basin is one of the main research intervals of continental shale gas. The shale pore structure is an important indicator for evaluating the reservoir capacity of shale reservoirs. We concentrate on the pore structure to indicate reservoir capacity using several testing methods, e.g. N2 adsorption-high pressure mercury pore size combined experiment, X-Ray Diffraction (XRD) and the total organic carbon (TOC) method. The results show that the clay mineral content of continental shale is high. The pore type is mainly the mineral matrix pore, followed by organic matter pore, the microcracks locally developed; the distribution interval of main pore size is mesopore between 10—50nm; the pore volume and specific surface area of the continental shale reservoirs is negatively correlated or unrelated to TOC, mainly due to the failure of pore development in the organic endoscopic and fusinite as well as the occupation of pore volume and adsorption site by soluble organic matter. The larger pores are mainly provided by clay minerals; the reservoir capacity of the continental shale reservoirs was evaluated by the two-factor evaluation method of pore volume and specific surface area. It was found that the continental shale is mainly composed of free reservoirs, and the reservoir capacity is mostly grade II-IV. The research results elucidate the pore structure characteristics and reservoir capacity of continental shale reservoirs in northeastern Sichuan Basin, having important theoretical and guiding significance for the gas-bearing evaluation and dessert target optimization of continental shale in the study area.